Pengaruh Penggunaan KB Suntik 3 Bulan dan Non-Kontrasepsi terhadap Siklus Menstruasi Wanita Usia Subur - Saputri, Nur; Ningsih, Nisa Kartika; Lestari, Siti (Universitas Baiturrahim, 2025)
The menstrual cycle is the distance between the start date of menstruation in the previous month and the start of menstruation in the following month. Normally the menstrual cycle lasts 28-35 days and menstruation occurs 11-13 times in one year. Every woman's menstrual cycle is said to be irregular or irregular if the cycle lasts less than 21 days or more than 35 days. The aim of this research was to determine the relationship between the use of 3-month injectable contraceptives and non-contraceptives with the menstrual cycle in women of childbearing age (WUS) in Praktik Mandiri Bidan Herawati, Am, East Tanjung Jabung District. The research method used is analytical with a retrospective approach. The population in this study were all women of childbearing age in 2022, totaling 40 respondents. The sampling technique used a total sampling technique of 40 people. Data analysis used the chi-square test. The research results showed that there was a relationship between 3-month injectable birth control and non-contraception with the menstrual cycle in women of childbearing age (WUS) at Praktik Mandiri Bidan Herawati, Am. Keb Tanjung Jabung Timur with a p-value of 0.001. The conclusion of this research is that there is a relationship between 3-month injectable birth control and non-contraception with the menstrual cycle in women of childbearing age (WUS) at Praktik Mandiri Bidan Herawati, Am. Keb Tanjung Jabung Timur. This research can be used as a prediction through early screening of risk factors for menstrual cycle disorders.